Assessing the impacts of pottery production relocation and its potential for tourism development in Chanh Nghia Village, Thu Dau Mot City, Binh Duong Province, Vietnam - Nguyen Huu Phi; Le Thi Thu Huong; Vilas Nitivattananon; Kim, Sohee Minsun (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
ChanhNghia pottery village is an ancient and famous pottery village in ChanhNghia Ward, Thu Dau Mot City, Binh Duong Province which is located in the East of Southern Vietnam. It is also a familiar place for many delegations and people when visit Binh Duong Province. However, since the relocation policy of Binh Duong government has started in 2004, which banned the ceramics production in urban area and relocated the kilns to the industrial estate, the pottery production in ChanhNghia village has considerably reduced from 36-37 kilns baking pottery throughout the day and night to only about 4-5 small pottery kilns. Consequently, the livelihood of people in the village has been changed significantly and the village is losing its cultural value as a famous traditional pottery heritage.Nevertheless, these issues have not been seriously studied and the problems seem to be out of attention of the government. This study, therefore, will assess the impacts of pottery production relocation on quality of life of people in Chanh Nghia village. It will also identify the potentials for tourism development in the village in order to propose solutions for improving the livelihood of people. The scope of this study focuses on those people who remain living in the village after the relocation, while excluding those who have relocated to other places. The quality of life is mainly consider the living condition of people, while the environmental pollution are excluded from this study. The primary data and information for this study are collected through different tools including field observations, questionnaire survey of 40 households, narrative story, focus group interview of 5-7 households representatives, and unstructured interviews with 11 key informants. In addition to primary data collection, the secondary data is also collected from different government reports and documents as well as newspapers. The study employs the mixed method for data analysis.The findings show that after the relocation, although the overall environment condition of the village was better, livelihood of people was seriously changed including impoverished income, bankrupt, selling land, changing career, and loosing skills in pottery production, etc. At the same time, the network of community was declined as people no longer work together on pottery production. However, the village has high potentials for tourism development due to its traditional and historical values, especially the special living characteristics and festivals of the Chinese community attracting a lot of tourists. Its location in the heart of Thu Dau Mot City with convenient traffic connection to other places is also very convenient for tourism. The majority of residents in the village are enthusiastic to develop tourism in their village for income generation and cultural value conservation. This also goes along with the development strategies of Binh Duong province{u2019}s government towards tourism development.
A project submitted in partial fulfillment of the requirements for the degree of Professional Master in Urban Management
Project (M. Sc.) - Asian Institute of Technology, 2015
Keywords: Tourism -- Vietnam -- Chanh Nghia Village; Pottery industry -- Evaluation -- Vietnam -- Chanh Nghia Village